Beacon based zoo information and activities reminder notification / Muhammad Zikrie Hasim - Hasim, Muhammad Zikrie (2018)
Zoo Negara is the most popular place to visit various animals especially during school holiday many parents bring their children to see animals. The main problem is as the visitor that comes from different countries they may have problem to gain information of the exhibited animals because of the language barrier. In Zoo Negara the information about exhibited animal will be display on the board only in language English and Malay only. This will be a barrier to visitors coming from other countries because they do not understand. The next issue is visitor will miss attending the animal’s show time and miss their lunch time because they are not aware of times as they are busy looking and capturing photos of the animals. This will be a limited of time for them to join any event or activity inside the zoo. One of the objective of this project is to develop a mobile application with beacon triggered animal information functionality that provides multi-languages. Next, to integrate lunch time and animal show time alert notification modules in a proposed mobile application. Android Studio will be used as development tool for this project and MySQL as a database to keep all data or information. Other than that the application can only be used only inside the zoo and this application is develop based on Android platform and hardware being used is Estimote beacon sensor.